Sex, violence and inequality. Women in the police - Sirimarco, Mariana (Universidad Nacional del Litoral, 2021)
The large number of cases of abuse and violence against Argentinean police women reveals an institutional and daily scenario. Paying attention to this matter implies two related movements. In the first place, one that makes us wonder about the practices that sustain the exercise of police power. In the second place, a movement that makes us take interest in the particular uses of sexuality that give sense to labor interactions in the police world. With these issues deals this paper: with the way in which sexual violence and sexuality relates to the formal and informal management of rights and professional tasks.